Strong tournaments with the fewest Hamiltonian paths - Moon J.W.; Yang, Laura L. M. (Utilitas Mathematica, 2007)
Busch recently determined the minimum number of Hamiltonian paths a strong tournament can have. We characterize the strong tournaments that realize this minimum.